2018
DOI: 10.1097/mcg.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Fidaxomicin Therapy in Clostridium difficile Infection

Abstract: All patients with a first CDI episode treated with fidaxomicin responded with no recurrences. Patients with prior CDI episodes were less likely to respond (especially with more than 1 prior episode) and more likely to recur, suggesting a greater clinical benefit of fidaxomicin earlier in the course of CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
0
31
0
1
Order By: Relevance
“…For patients with IBD, a known risk factor for CDI [ 21 ], our study found that resolution of diarrhoea occurred in a similar proportion of treatment episodes (81.8%) to that for patients without any MCSI (83.3%). In comparison, a previous open-label study of fidaxomicin reported that resolution of diarrhoea occurred in 90% of the overall patient population but 100% of patients with IBD [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…For patients with IBD, a known risk factor for CDI [ 21 ], our study found that resolution of diarrhoea occurred in a similar proportion of treatment episodes (81.8%) to that for patients without any MCSI (83.3%). In comparison, a previous open-label study of fidaxomicin reported that resolution of diarrhoea occurred in 90% of the overall patient population but 100% of patients with IBD [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…The recurrence rate of 24.4% was higher than those reported in the 2 phase 3 clinical trials (~13%‐15%) . Other real‐world descriptive studies have reported variable recurrence rates of 10%‐21% . For example, Eiland and colleagues reported the clinical outcomes of sixty patients who received fidaxomicin for CDI, of which 43.3% were treated for recurrent CDI; 10.3% of patients who achieved clinical success experienced recurrent CDI within 90 days of completing fidaxomicin therapy .…”
Section: Discussionmentioning
confidence: 95%
“…Fifteen per cent of patients experienced recurrence within 8 weeks of the onset of the previous episode; the recurrence rate was higher among patients treated for recurrent CDI than those treated for an initial episode (8% vs 26%, P = .04) . Spiceland and colleagues demonstrated a recurrence rate of 19% within 8 weeks of completing treatment among 81 patients who received fidaxomicin at Mayo Clinic sites in Minnesota, Florida and Arizona, including 61 patients (75%) with recurrent CDI . In the study by Shah and colleagues, the recurrence rate of CDI after treatment with fidaxomicin was 21% within 90 days of initiation of fidaxomicin among 102 patients from 11 US hospitals, including 64% with recurrent CDI and 68% with severe CDI .…”
Section: Discussionmentioning
confidence: 98%
“…В рандо мизированном стратифицированном подисследовании у пациентов с первым рецидивом ИКД последующий вто рой рецидив встречался реже после терапии фидаксо мицином в сравнении со стандартным 10дневным кур сом ванкомицина (19,7% против 35,5%; P=0,045) [343]. Результаты пострегистрационного неконтролируемого применения фидаксомицина предполагают менее эффек тивные ответы в отношении излечения и последующего рецидива после терапии у пациентов с рецидивирующей ИКД, особенно в случае ≥2 рецидивов [344]. Перораль ный ванкомицин следует использовать в виде курсов с постепенным снижением дозы или в виде пульсрежима, если для начального эпизода использовался стандарт ный 10дневный курс ванкомицина.…”
Section: резюме по научному обоснованиюunclassified